2018
DOI: 10.1007/s13201-018-0832-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the transfer of dissolved solutes from soil into surface runoff on loess slopes in China

Abstract: Overland flow and concomitant solute transport were a major source of pollutants in receiving surface water. The objective of this study was to better understand the mechanisms of soil erosion, solute transport from soil to runoff and lost via runoff, especially the effects of cumulative infiltration before the runoff generation. Laboratory experiments were conducted with three initial soil moisture contents, three rainfall intensities and three slope gradients to evaluate the effects of these variables and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…; raindrop size and amount, storm duration and velocity of raindrops, rainfall intensity were the main rainfall factor as an intense storm produces high kinetic energy because high-intensity storm contains a greater percentage of energy to impact on the soil. An experimental study conducted by Dong et al (2018) tested the rainfall intensities of 60, 96, and 129 mm/hr under similar conditions and found that the high intensity produces the highest soil content in the runoff. The nding is similarly found in Almeida et al (2021) where the highest rainfall intensity varied from 75.0 to 44.6 mm h-1 produced a maximum sediment yield (0.138 g m-2 min-1) and runoff rates (0.87 mm min-1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; raindrop size and amount, storm duration and velocity of raindrops, rainfall intensity were the main rainfall factor as an intense storm produces high kinetic energy because high-intensity storm contains a greater percentage of energy to impact on the soil. An experimental study conducted by Dong et al (2018) tested the rainfall intensities of 60, 96, and 129 mm/hr under similar conditions and found that the high intensity produces the highest soil content in the runoff. The nding is similarly found in Almeida et al (2021) where the highest rainfall intensity varied from 75.0 to 44.6 mm h-1 produced a maximum sediment yield (0.138 g m-2 min-1) and runoff rates (0.87 mm min-1).…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall especially with higher intensity increases the risk of soil erosion and eventually nutrient loss. Dong et al (2018) investigated the solute transport by using Potassium Bromide as a tracer and concluded that solute content in runoff is related to the sediment mass by showing that; a) under initial moisture content of 15% and 25%, the solute content was 1.51 and 2.63 times greater than when the initial moisture content was 5%, respectively, b) the higher the rainfall intensity applied, the higher the amount of runoff solute content and c) under slope gradient of 15° and 25°, the solute content was 1.43 and 3.51 times greater than when slope gradient was 5°, respectively. Dai et al (2018) have studied the amount of nitrogen (TN) and phosphorus (TP) losses under natural rainfall events and found that sediment yield is the major controller of the TN and TP loss.…”
Section: Introductionmentioning
confidence: 99%